2016
DOI: 10.1016/j.jad.2015.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Affective instability, childhood trauma and major affective disorders

Abstract: Background Affective instability (AI), childhood trauma, and mental illness are linked, but

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…Some studies (Etain et al, 2008;Marwaha et al, 2016) showed that BD type 1 subjects with a history of childhood trauma had higher affective instability than those without such a history. ADHD is considered as a neurodevelopmental disorder with symptoms such as impulsivity and attention deficits often arising early in the life of an individual and sometimes disrupting the crucial link with the caregivers ultimately leading to childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (Etain et al, 2008;Marwaha et al, 2016) showed that BD type 1 subjects with a history of childhood trauma had higher affective instability than those without such a history. ADHD is considered as a neurodevelopmental disorder with symptoms such as impulsivity and attention deficits often arising early in the life of an individual and sometimes disrupting the crucial link with the caregivers ultimately leading to childhood trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It is also independently linked to greater medication use and detention under mental health legislation (Patel et al, 2015). It is associated with childhood trauma experiences (including abuse) and it is suggested that it may partly explain the connection between these and psychiatric disorders (Aas et al, 2016;Marwaha et al, 2016;Moffa et al, 2017). The estimated prevalence of AI in the general population is 14%, with levels being higher in younger people and women (Marwaha et al, 2013c;Patel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term psychological and somatic consequences of childhood trauma have been well validated in an extensive body of research [3][4][5][6][7][8][9]. Central Nervous system (CNS) sensitization is an utmost probable contributor leading to these late consequences [10]. However, its mechanisms are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%